Increased physical effort overrides the potentially deleterious effects of resource depletion following self-control - Fullerton, C.; Lane, A. M.; Devonport, T. J. (Journal of Science and Cycling, 2014)
Background: Long duration cycling events require riders to maintain concentration and self-control over lengthy periods, for example, listening to race plans and/or eve-dropping on conversations of other riders whilst maintaining pace and bike control. Self-control is the deliberate effort to override a dominant response such as an emotion or thought with a response perceived to benefit goal attainment. Evidence suggests that self-control is an effortful process that draws upon both physiological and psychological resources (Gailliot et al., 2007: Journal of Personality and Social Psychology, 92 (2), 325-336). Thus, if effortful self-control draws upon physiological resources, then it could hamper endurance performance which utilises the same physiological substrates. However, recent research has questioned this explanation suggesting self-control might be more about resource allocation (Beedie & Lane, 2012: Personality and Social Psychology Review, 16(2):143-53). Purpose: The purpose of the present study was to examine the effects of doing self-control tasks on cycle performance and emotion regulation. In a dual-task design, one task (bicycle ride) was personally meaningful and a second task (Stroop task) had unknown personal meaning. We hypothesised that by recruiting participants to a task that was personally meaningful, individuals` emotions would act as a signal to mobilise resources to overcome the potentially deleterious effects of resource-depletion deriving from the Stroop task. We predicted that performance on the Stroop task would deteriorate as participants re-allocated resources to the primary task. Methods: 43 participants were randomly assigned to one of two conditions: an experimental condition comprising two self-control tasks performed consecutively and a control condition in which two tasks were performed consecutively but only one required self-control. The procedure was as follows: 1) Stroop task 2) Bicycle ride; 3) Stroop task; 4) Bicycle ride, 5) Stroop task. A modified version of the classic Stroop colour-word task was employed using shapes and colours. In the (non-depleting) control condition, shapes were presented in their respective shape and colour (e.g., the word ``green`` and shape "triangle" was presented in green ink and as a triangle). In the (depleting) experimental condition, the word and ink colour was incongruent with the shape (e.g., the words "green triangle" appeared below a red square in red font colour). Participants rated their emotions before and after both bicycle rides. They were all asked to rate how important it was to perform well. Results: Cycle performance results indicated performance was fastest in the second trial (194 + 48s vs 212 + 45s) than the first trial (213 + 39s vs 230 + 41s) with no significant differences between the control and experimental group, hence suggesting the first self-control did not impair performance. Improved performance was matched with increased heart rate across trials for both the control (130 + 19bpm vs 136 + 19bpm) and experimental groups (125 + 22 vs 133 + 21bpm). In contrast, the rate of improvement for the Stroop was significantly faster among the control group compared to the experimental group across all three tasks (18.38 + 5.27 vs 24.17 + 5.67s; 17.54 + 4.86 vs 23.12 + 4.51; 16.39 + 4.70 vs 22.0.8 + 3.25). Discussion: In support of our hypothesis, bicycle performance improved following completion of the Stroop task. In contrast to previous findings, final Stroop performance also improved suggesting that there could be a transfer effect. Our findings are consistent with recent research that has argued that cognitive and affective theory (Beedie & Lane, 2012) provides a better fit to deficits in self-control than the strength model (Gailliot et al., 2007). Conclusion: These findings provide experimental evidence that self-control ability is temporarily impaired following a separate, unrelated self-control task. However, if participants are sufficiently motivated to perform well, then increased physical effort may improve self-control behaviour and this appears to transfer across tasks.